Evaluating the effects of curcumin nanomicelles on clinical outcome and cellular immune responses in critically ill sepsis patients: A randomized, double-blind, and placebo-controlled trial - Karimi, Arash; Pourreza, Sanaz; Vajdi, Mahdi; Mahmoodpoor, Ata; Sanaie, Sarvin; Karimi, Mozhde; Tarighat-Esfanjani, Ali (Frontiers in Nutrition, 2022)
Introduction In sepsis, the immune system is overreacting to infection, leading to organ dysfunction and death. The purpose of this study was to investigate the impacts of curcumin nanomicelles on clinical outcomes and cellular immune responses in critically ill sepsis patients. Method For 10 days, 40 patients in the intensive care units (ICU) were randomized between the nano curcumin (NC) and placebo groups in a randomized study. We evaluated serum levels of biochemical factors, inflammatory biomarkers, the mRNA expression levels of FOXP3, NLRP-3, IFN-γ, and NF-κp genes in the PBMCs, and clinical outcomes before the beginning of the supplementation and on days 5 and 10. Results NLR family pyrin domain containing 3 (NLRP3), interferon gamma (IFN-γ), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) mRNA expression levels significantly P = 0.014, P = 0.014, and P = 0.019, respectively) decreased, but forkhead box P3 (FOXP3) mRNA expression levels increased significantly (P = 0.008) in the NC group compared to the placebo group after 10 days. NC supplementation decreased serum levels of IL-22, IL-17, and high mobility group box 1 (HMGB1) (P < 0.05). Nevertheless, biochemical factors and nutritional status did not differ significantly (P > 0.05). NC supplementation resulted in decreased sequential organ failure assessment and multiple organ dysfunction syndromes scores, while it did not have significant impacts on length of stay in the ICU, systolic blood pressure, diastolic blood pressure, a saturation of oxygen (%), and respiratory rate (breaths/min) PaO2/FiO2 (p > 0.05). Conclusion For critically ill patients with sepsis, NC supplementation may be an effective therapeutic strategy. More randomized clinical trials involving longer follow-up periods and different doses are needed to achieve the best results.